Changes in soil bacterial community and functions by substituting chemical fertilizer with biogas slurry in an apple orchard - Zhang, He; Ma, Yue; Shao, Jianzhu; Di, Rui; Zhu, Feng; Yang, Zhichang; Sun, Jianshe; Zhang, Xueying; Zheng, Chunyan (Frontiers in Plant Science, 2022)
Growing concerns about the negative environmental effects of excessive chemical fertilizer input in fruit production have resulted in many attempts looking for adequate substitution. Biogas slurry as a representative organic fertilizer has the potential to replace chemical fertilizer for improvement of sustainability. However, it is still poorly known how biogas slurry applications may affect the composition of soil microbiome. Here, we investigated different substitution rates of chemical fertilizer with biogas slurry treatment (the control with no fertilizer and biogas slurry, CK; 100% chemical fertilizer, CF; biogas slurry replacing 50 % of chemical fertilizer, CBS; and biogas slurry replacing 100 % of chemical fertilizer, BS) in an apple orchard. Soil bacterial community and functional structure among treatments were determined using Illumina sequencing technology coupled with Functional Annotation of Prokaryotic Taxonomy (FAPROTAX) analysis. Leaf nutrient contents, apple fruit and soil parameters were used to assess plant and soil quality. Results showed that most of fruit parameters and soil properties were significantly varied in the four treatments. CBS treatment increased the contents of soil organic matter, alkali nitrogen and available potassium average by 49.8%, 40.7% and 27.9%, respectively. Treatments with biogas slurry application increased the single fruit weight, fresh weight, and dry weight of apple fruit average by 15.6%, 18.8% and 17.8, respectively. Soil bacterial community dominance and composition were significantly influenced by substituting of chemical fertilizer with biogas slurry. Biogas slurry application enhanced the relative abundance of some beneficial taxa (e.g. Acidobacteria Gp5 and Gp7, Parasegetibacter) and functional groups related to carbon and nitrogen cycling such as chemoheterotrophy, cellulolysis, and nitrogen fixation. Soil available phosphorus and potassium, pH and electrical conductivity were identified having a high potential for regulating soil bacterial specific taxa and functional groups. This study showed that the proper ratio application (50%: 50%) of biogas slurry with chemical fertilizer could regulate soil bacterial composition and functional structure via changes in soil nutrients. The variations of bacterial community could potentially take significant ecological roles in maintaining apple plant growth, soil fertility and functionality.